Coating Scaffold Hidroksiapatit Dengan Kitosan Menggunakan Metode DIP - Coating - Arosyidin Arosyidin; Ahmad Fadli; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Bone implants are a tissue replacement technique using synthetic materials that are compatible with body tissues. Materials that can be used as a bone implant one of them is hydroxyapatite scaffold (HA). However, most of the HA scaffolds still have one of the strongest compression values. To increase the compressive strength of the scaffold it must be coated with other polymers. One of the polymers that is biodegradable with the body is chitosan. HA scaffold coating method using dip - coating method by dissolving chitosan powder into acetic acid concentration 0,50%; 0.75% and 1.00% (w / v). Next, scaffold HA in coating with chitosan solution for 30, 45, 60 minutes. After coating, HA scaffold is dried at room temperature for 24 hours. The increase of chitosan concentration 0,50% to 0,75% can decrease the porosity that is 78% to 76% and pore size from 28,25 μm become 22,88 μm. Furthermore, the longer coating time required 30 minutes and 60 minutes then the greater the compressive strength of HA scaffold produced is 1.43 MPa to 4.05 MPa. The optimum condition of the operation is 0.75% chitosan concentration and 60 minutes coating time with a compressive strength value of 4.05 MPa.Keywords: chitosan, coating, compressive strength, hydroxyapatite, scaffold